HUBUNGAN RASA MALU DENGAN KESEPIAN PADA MAHASISWA BARU PERANTAU YANG TINGGAL DI APARTEMEN. - Marisya Pratiwi; Artha Nimas Asih (Universitas Paramadina, 2019)
The study aims to determine the relationship of between shyness and loneliness in college students whom living in apartment. Participants for this research were 195 Sriwijaya University students, grade of 2016 and 2017, whom living in Apartments Indralaya. They were taken through purposive sampling. The scales used were the loneliness scale based on loneliness responses according to Rubenstein and Shaver (1982) and the scale of shyness based on the characteristics of shyness according to Henderson and Zimbardo (1998). Data analysis used Pearson Product Moment correlation. The pilot study of the measuring scales was conducted with 60 student with same characteristics. The results of the study that there is a significant relationship between shyness and loneliness in students whom living in apartment. Keywords: Shyness, Loneliness, student, apartment